2002
DOI: 10.1007/s001980200012
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D and Muscle Function

Abstract: The aim of this review is to summarize current knowledge on the relation between vitamin D and muscle function. Molecular mechanisms of vitamin D action on muscle tissue have been known for many years and include genomic and non-genomic effects. Genomic effects are initiated by binding of 1,25-dihydroxyvitamin D3 (1,25(OH)2D) to its nuclear receptor, which results in changes in gene transcription of messenger RNA and subsequent protein synthesis. Non-genomic effects of vitamin D are rapid and mediated through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
267
1
29

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 447 publications
(308 citation statements)
references
References 70 publications
(94 reference statements)
2
267
1
29
Order By: Relevance
“…63,64 The vitamin D receptor and intracellular vitamin D regulation have also been identified in heart muscle, liver, lung and adrenal systems, all of which are determinants of athletic performance. 13,65,66 However, the direct evidence for treatment of vitamin D deficiency to improve performance is extremely weak. Highquality trials in athletic populations are required to determine the effects of correcting vitamin D deficiency and insufficiency on athletic, and particularly muscular, performance.…”
Section: Discussionmentioning
confidence: 99%
“…63,64 The vitamin D receptor and intracellular vitamin D regulation have also been identified in heart muscle, liver, lung and adrenal systems, all of which are determinants of athletic performance. 13,65,66 However, the direct evidence for treatment of vitamin D deficiency to improve performance is extremely weak. Highquality trials in athletic populations are required to determine the effects of correcting vitamin D deficiency and insufficiency on athletic, and particularly muscular, performance.…”
Section: Discussionmentioning
confidence: 99%
“…A deficiência de vitamina D está associada a uma menor mineralização do tecido osteóide caracterizando a osteomalácia (8,11). Entretanto, análises mais recentes demonstram que valores não tão reduzidos de vitamina D estão associados a aumento do turnover ósseo e conseqüente aumento de fraturas.…”
Section: Discussionunclassified
“…A população geriátrica é mais sensível à hipovitaminose D por vários motivos, dentre eles por se expor menos ao sol, ter sua capacidade de produção cutânea de vitamina D reduzida (6)(7)(8), alimentar-se de forma inadequada (9)(10)(11)(12), absorver menos vitamina D pelo trato gastrintestinal (3), usar múltiplas drogas que interferem na absorção/metabolização da vitamina D e apresentar comprometimento renal (3). Dentro deste grupo, pacientes institucionalizados têm um risco ainda maior para esta situação (13), que se reflete em um aumento de até 10,5 vezes no risco de fratura (14).…”
Section: Introductionunclassified
“…Some studies have suggested that one important effect of vitamin D is that it improves muscular function, which in turn would contribute to reducing falls (Pfeifer et al, 2002;Bischoff et al, 2003). The mechanisms most frequently associated with vitamin D effects are an increase in intestinal calcium absorption, a decrease in PTH secretion, and a diminution in the rate of bone remodeling (Chapuy et al, 1992;DawsonHughes et al, 1997).…”
Section: Discussionmentioning
confidence: 99%